2019
DOI: 10.1007/s11846-019-00329-4
|View full text |Cite
|
Sign up to set email alerts
|

Participation in crowdfunding among users of collaborative platforms: the role of innovativeness and social capital

Abstract: This work aims to elucidate the profile of participants in crowdfunding initiatives among users of collaborative platforms, considering them as agents with a high likelihood of taking part in these initiatives due to being users of digital services. This delimitation is performed by investigating the link between two intrinsic factors (innovativeness and social capital) and participation in crowdfunding initiatives. After the analysis of a sample generated by the Sociological Research Centre (CIS) of 422 users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Digital technologies can take various forms including platforms (Clauss et al 2018a), big data and artificial intelligence (O'Leary 2013), 3D printing (Bouncken et al 2019b), block-chain (Morkunas et al 2019), and practices tightly related to technology use, for example crowdfunding (Bouncken et al 2014;Medina-Molina et al 2019). The digitalization and its business models strongly build firm's growth (Laamanen et al 2018;Teece and Linden 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Digital technologies can take various forms including platforms (Clauss et al 2018a), big data and artificial intelligence (O'Leary 2013), 3D printing (Bouncken et al 2019b), block-chain (Morkunas et al 2019), and practices tightly related to technology use, for example crowdfunding (Bouncken et al 2014;Medina-Molina et al 2019). The digitalization and its business models strongly build firm's growth (Laamanen et al 2018;Teece and Linden 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Social capital refers to the resources people can access from their social connections and networks (Dickinson et al, 2017;Sigerson & Cheng, 2018). The literature has shown that social capital influences community issues like crowdfunding and social media (Medina-Molina et al, 2019;Weiler et al, 2022;Zhang et al, 2022). Therefore, social capital is dependent on the relationships between people and their connections to the community (Okoli & Oh, 2007;Wang et al, 2018).…”
Section: Social Capital Theorymentioning
confidence: 99%
“…Thus, social network ties have different roles in attracting backers to crowdfunded campaigns (Foster 2019), explaining the effect of network centrality. Moreover, innovation and social capital have an interactive effect on the willingness to participate in crowdfunding (Medina-Molina et al 2019).…”
Section: Influence Of Social Connections On Funding Outcomesmentioning
confidence: 99%